Least-Squares Adaptation of Affine Combinations of Multiple Adaptive Filters - Azpicueta Ruiz, L.A.; Zeller, Marcus; Figueiras-Vidal, Anibal R.; Arenas-Garcia, Jeronimo (2010 IEEE International Symposium on Circuits and Systems, 2010)
Adaptive combinations of adaptive filters are gaining popularity as a flexible and versatile solution to improve adaptive filters performance. In the recent years, combination schemes have focused on two different approaches: Convex and affine combinations, developing principally practical implementations with just two component filters. However, combinations of a higher number of adaptive filters can offer additional advantages, mainly in tracking environments. In this paper, we introduce a practical adaptation scheme for the affine combination of an arbitrary number of filters, including a steady-state analysis where the proposed rule is compared with the optimal combination. Several experiments both in tracking and stationary scenarios serve to demonstrate the appropriate performance of this approac
LMS::842